Association between Maternal Dietary Patterns and Preeclampsia Incidence: A Cross-Sectional Study at Rehatta Hospital, Indonesia - Dary, Dary; Tampubolon, Rifatolistia; Tauho, Kristiani Desimina; Tobing, Tegar Anggiama; Mangalik, Gelora (Media Publikasi Cendekia Indonesia, 2025)
Preeclampsia is a severe pregnancy disorder and causes high maternal mortality rates in Indonesia, with 1,077 cases in 2021. This study aims to investigate the association between maternal dietary patterns and the incidence of preeclampsia, particularly among pregnant women in Jepara Regency, a coastal region. This study is a quantitative correlational study, with the population being all mothers with a gestational age above 20 weeks who underwent examinations at Rehatta Hospital, Jepara Regency. Respondents were determined by consecutive sampling, obtaining 50 pregnant women who underwent pregnancy checks during August-September 2024. Data on maternal dietary patterns were obtained by filling out the FFQ (Food Frequency Questionnaire) sheet. Data on the incidence of preeclampsia were determined based on a doctor's diagnosis. The collected data were analyzed univariately and bivariately using SPSS software. The Pearson test results for carbohydrate diet obtained p-value = 0.001, animal side dishes p-value = 0.001, vegetable side dishes p-value = 0.007, vegetables p-value = 0.001, fruits p-value = 0.001, fast food p-value = 0.001, and drinks p-value = 0.056. Based on the seven nutrients and drinks, high carbohydrate intake, lack of animal side dishes, vegetables, fruit, irregular eating, and fast food consumption have p-values ​​<0.05, meaning maternal diet has a significant relationship with the incidence of preeclampsia. This finding confirms that a balanced diet during pregnancy plays a vital role in preventing preeclampsia. Therefore, monitoring diet and nutritional education for pregnant women needs to be a focus in efforts to prevent preeclampsia in health services